Motor dysfunction of the gut in cystic fibrosis. Issue 9 (31st May 2020) - Malagelada, Carolina; Bendezú, R‐Alvaro; Seguí, Santi; Vitrià, Jordi; Merino, Xavier; Nieto, Adoracion; Sihuay, Denisse; Accarino, Anna; Molero, Xavier; Azpiroz, Fernando
Abstract: Background: Cystic fibrosis (CF) is a multisystem disease caused by mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) protein. Cystic fibrosis transmembrane conductance regulator is extensively expressed in the intestine and has an important role in the regulation of the viscosity and pH of gut secretions. Several studies have reported a delay in small bowel and colonic transit times in patients with CF which have been attributed to the secretory dysfunction. Our aim was to determine whether intestinal contractility is affected in these patients. Methods: Consecutive patients with CF referred to our institution between 2014 and 2017 (n = 16) were prospectively investigated using automated non‐invasive techniques for morpho‐functional evaluation of the gut developed in our laboratory. On separate days, intraluminal images of the gut were obtained by capsule endoscopy and external images by abdominal MRI. Analysis of images (endoluminal and external) was performed with original, previously validated programs based on computer vision and machine learning techniques and compared with age‐ and sex‐matched controls. Key Results: Patients with CF exhibited important reduction in contractile activity and increased retention of static turbid luminal content in the small bowel by endoluminal image analysis. Morpho‐volumetric analysis of MRI images found increased ileo‐colonic volumes in CF. Significant correlations between abnormalities detected by intraluminal and external imaging techniques were found. The presence and severity of digestive symptoms were not related to abnormal gut function. Conclusion and Inferences: Impaired transit and pooling of gut contents in patients with CF is associated with impaired intestinal motility. Abstract : Patients with cystic fibrosis exhibited an important reduction in contractile activity and increased retention of static turbid luminal content in the small bowel by endoluminal image analysis. These findings indicate that impaired transit and pooling of gut contents in patients with cystic fibrosis are not only related to the secretory dysfunction and thickening of intraluminal contents, but also to a motor dysfunction of the gut.